101 Interactive STEM Activities: An E-Book to generate interest in STEM fields among preschoolers / Nor Shamimi Muhamad Ridza, Yarina Ahmad and Thenmolli Vadeveloo - Muhamad Ridza, Nor Shamimi; Ahmad, Yarina; Thenmolli, Vadeveloo (2021)
STEM education refers to a concept that integrates four main subjects which are Science, Technology, Engineering, and Mathematics. In this modern world, where early childhood learning needs to adapt to the significant environmental changes that have occurred over the last decade, STEM education is the right tool to enhance children's skills in learning especially in critical and creative thinking. Through STEM, children learn to explore, observe, question and answer, and also take part in fun activities that are related to what is happenings around the world. Hence, it is important to ensure that STEM fields must be applied in formal education even among preschoolers. Despite knowing the importance of STEM education, many preschool educators are still having issues in implementing STEM activities. STEM education is known as difficult to implement in preschools since it is time-consuming and requires teachers' creativity through the process. Some of the teachers also have some issues with the lack of knowledge and information on how to conduct STEM-related activities. Therefore, this e-book is produced to help preschool teachers and educators implementing effective and efficient STEM activities. There are 101 suggestion activities with a list of items needed, together with a link and QR code on how the activities are being conducted. This e-book will give benefits not only to the teachers and educators but also parents as some of the teacher's roles have been transferred to the parents since the Covid-19 pandemic hit the world.